Application of GeoGebra-Assisted Problem-Based Learning Model to Strengthen the Learning Interest of Eighth Grade Junior High School Students - Sihombing, Willy Ruben; Dirgantoro, Kurnia Putri Sepdikasari; Bonyah, Ebenezer (EDUPEDIA Publisher, 2025)
Learning interest is a psychological drive that allows students to learn something consciously, calmly, and with discipline. A lack of learning interest was observed in one school in West Jakarta. This is a significant issue as learning interest directly impacts the quality of education. Therefore, the purpose of this study is to investigate the application of a GeoGebra-assisted problem-based learning (PBL) model to enhance the learning interest of eighth-grade junior high school students. Additionally, the paper will discuss the application of this GeoGebra-assisted PBL model from a Christian perspective. This research utilizes a descriptive qualitative method, with data collected through observation sheets, lesson plans, and teacher reflection sheets. The analysis of the research data demonstrates the positive effect of the GeoGebra-assisted PBL model on learning interest. This is evidenced by observed changes in student behavior that align with the indicators of learning interest. Thus, it can be concluded that the application of the GeoGebra-assisted PBL model can foster and strengthen students' learning interest. The PBL model offers a platform for student exploration, with GeoGebra acting as a supportive tool. The diverse features of GeoGebra facilitate the learning process, thereby fostering a sense of enjoyment and interest. However, due to certain limitations in its application, educators must guide students in its use.